Analisis Asuhan Keperawatan dengan Intervensi Terapi Foot Massage Untuk Nyeri pada Ibu Post Sectio Caesarea di RS Bhayangkara Tk. I R. Said Sukanto - Esther Novita Angelia (2022)
Sectio caesarea is a surgical procedure to deliver the fetus through an abdominal incision and uterine incision. Pain is one of the outcomes that are most often experienced. If not treated, the pain will impact both the mother and baby, such as disturbed mother's activities, limited activity in daily living of the mother, unfulfilled baby nutrition due to delayed breastfeeding, lack of baby care, and the unfulfilled bond of love between mother and baby. Foot massage is one of the non-pharmacological techniques that can be done to reduce pain in post sectio caesarea mothers. The purpose of this study is to analyze nursing care with foot massage therapy interventions to treat acute pain in post sectio caesarea mothers. There are 2 post sectio caesarea mothers that participated in this study. The foot massage therapy is given to one mother. For three days, foot massage was carried out once per day for 20 minutes. the Numerical Rating Scale (NRS) is used to measure the level of pain. The results of this study show that after being given foot massage therapy intervention, one patient's pain scale is decreased from a scale of 2 to a scale of 6. Meanwhile, another patient who is not given a foot massage had a pain scale decrease from a scale of 4 to a scale of 7. Foot massage as a non-pharmacological therapy is proven to be able to reduce pain levels in postpartum mothers who undergo caesarean section without causing side effects.